2006
DOI: 10.1111/j.1365-2826.2006.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

A Population of Non‐Luteinising Hormone/Non‐Adrenocorticotrophic Hormone‐Positive Cells in the Male Rat Anterior Pituitary Responds Mitotically to Both Gonadectomy and Adrenalectomy

Abstract: The male rat anterior pituitary responds highly reproducibly to specific hormonal stimuli in terms of the extent and timing of mitotic and apoptotic (trophic) activity. The principal objective of the present study was to define the contribution of hormonally identifiable cells to the trophic responses to bilateral gonadectomy and bilateral adrenalectomy. The patterns of pituitary mitotic responses to adrenalectomy and gonadectomy are similar in amplitude and duration. When adrenalectomy and gonadectomy are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 29 publications
10
63
2
1
Order By: Relevance
“…Other studies have also shown lack of co-localization of BrdU in corticotrophs following adrenalectomy (Gulyas et al, 1991;Nolan & Levy, 2001;Taniguchi et al, 1995). Nolan and Levy, (Nolan & Levy, 2006) also reported a minor incidence of mitogenesis in corticotrophs or gonadotrophs following 3-and 6-days adrenalectomy or gonadectomy in rats. In the latter study, there was no additivity of mitogenic responses to adrenalectomy and gonadectomy, supporting the view that mitogenesis in response to both stimuli occurs in an undifferentiated progenitor population (Nolan & Levy, 2006).…”
Section: Alternative Actions Of Vp In the Pituitary On Mitogenesismentioning
confidence: 91%
“…Other studies have also shown lack of co-localization of BrdU in corticotrophs following adrenalectomy (Gulyas et al, 1991;Nolan & Levy, 2001;Taniguchi et al, 1995). Nolan and Levy, (Nolan & Levy, 2006) also reported a minor incidence of mitogenesis in corticotrophs or gonadotrophs following 3-and 6-days adrenalectomy or gonadectomy in rats. In the latter study, there was no additivity of mitogenic responses to adrenalectomy and gonadectomy, supporting the view that mitogenesis in response to both stimuli occurs in an undifferentiated progenitor population (Nolan & Levy, 2006).…”
Section: Alternative Actions Of Vp In the Pituitary On Mitogenesismentioning
confidence: 91%
“…The mechanisms underlying these changes are poorly understood. Fluctuations in the rate of cell division and cell death in the differentiated endocrine cell populations could explain some of the changes, but direct studies of the pituitary mitotic responses after stimuli that increase the number of ACTH and LH cells show that these changes do not arise by cell division from mature endocrine cells but rather by differentiation from uncommitted progenitors (6). Furthermore, it is difficult to explain the remarkable ability of the adult pituitary gland to repopulate after extreme loss of specific cell populations by genetic (7) or immune (8) lesions without the involvement of a multipotent stem or progenitor population in the adult gland (reviewed in refs.…”
mentioning
confidence: 99%
“…While differentiated endocrine cells can divide, but do so rarely, Nolan and Levy were the first to observe that, after adrenalectomy and/or gonadectomy, proliferation is essentially restricted to non-endocrine cells of an immature appearance. Moreover, double ablations do not have an additive proliferative effect, suggesting that a single population of undifferentiated cells responds to both adrenalectomy and gonadectomy (Nolan and Levy 2006). More recently, diphtheria toxin-mediated endocrine cell ablation experiments confirmed these results by showing a mobilization of SOX2-positive cells, with a transient induction of proliferation and, presumably, differentiation.…”
Section: Hypothalamusmentioning
confidence: 87%
“…Induction of apoptosis upon cell division, using specific genetic tools, confirmed this hypothesis by demonstrating that corticotroph turnover relies on the proliferation of differentiated cells (Langlais et al 2013). A physiological role for pituitary stem cells was initially suggested by studies investigating models of pituitary target organ ablation (Nolan and Levy 2006). It has been known for some time that ablation of the adrenals and/or gonads triggered a transient mitotic wave in the gland, followed by generation of increased numbers of endocrine cells; moreover, these were specifically the type that normally regulates the ablated organ.…”
Section: Hypothalamusmentioning
confidence: 92%